2017
DOI: 10.1021/acs.analchem.7b01728
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning on Signal-to-Noise Ratios Improves Peptide Array Design in SAMDI Mass Spectrometry

Abstract: Emerging peptide array technologies are able to profile molecular activities within cell lysates. However, the structural diversity of peptides leads to inherent differences in peptide signal-to-noise ratios (S/N). These complex effects can lead to potentially unrepresentative signal intensities and can bias subsequent analyses. Within mass spectrometry-based peptide technologies, the relation between a peptide’s amino acid sequence and S/N remains largely nonquantitative. To address this challenge, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In their experiment, RF and SVM with fine-tuned parameters achieved superior performance in discrimination between original sample from Korea and blended samples with accuracy generally above 95%. Albert Y. Xue [ 58 ] presented a machine-learning based method to address the problem of the large nonquantitative relationships between the peptide's amino acid sequence and peptide signal-to-noise ratios (SNR). Random forest was applied to predict the peptide's SNR by its amino acid sequence with Q-squared value of 0.59, which confirmed that the amino acid sequence could be used to predict SNR values of peptide.…”
Section: Methodsmentioning
confidence: 99%
“…In their experiment, RF and SVM with fine-tuned parameters achieved superior performance in discrimination between original sample from Korea and blended samples with accuracy generally above 95%. Albert Y. Xue [ 58 ] presented a machine-learning based method to address the problem of the large nonquantitative relationships between the peptide's amino acid sequence and peptide signal-to-noise ratios (SNR). Random forest was applied to predict the peptide's SNR by its amino acid sequence with Q-squared value of 0.59, which confirmed that the amino acid sequence could be used to predict SNR values of peptide.…”
Section: Methodsmentioning
confidence: 99%
“…It is already becoming difficult to fully understand the large data sets that are generated form peptide arrays, and as arrays increase in size, it will be more important to develop and apply complex analytical methods. A recent example from our group demonstrates the role of machine learning for more efficient peptide array design …”
Section: Applicationsmentioning
confidence: 99%
“…This reaction product can then be quantitated with matrix-assisted laser desorption/ionization mass spectrometry, which reveals peaks corresponding to both the substrate and product (and any intermediates or additional products). The SAMDI-MS method is compatible with the common 384 and 1536 spot formats and has been used to profile enzymes with peptide arrays. ,, We also recently demonstrated SAMDI could be used to profile the activity of a PTP on a phosphopeptide array . Becker and co-workers’ recent advance in studying protein–protein interactions using protein arrays and MALDI-MS also demonstrates the power of combining these technologies. , …”
Section: Introductionmentioning
confidence: 96%
“…The SAMDI-MS method is compatible with the common 384 and 1,536 spot formats and has been used to profile enzymes with peptide arrays. 23, 31, 3943 We also recently demonstrated SAMDI could be used to profile the activity of a PTP on a phosphopeptide array. 44 Becker and coworkers’ recent advance in studying protein-protein interactions using protein arrays and MALDI-MS also demonstrates the power of combining these technologies.…”
Section: Introductionmentioning
confidence: 99%